Promotion of natural tooth repair by small molecule GSK3 antagonists - Neves, Vitor C. M. (Sci Rep, 2017)
The restoration of dentine lost in deep caries lesions in teeth is a routine and common treatment that involves the use of inorganic cements based on calcium or silicon-based mineral aggregates. Such cements remain in the tooth and fail to degrade and thus normal mineral volume is never completely restored. Here we describe a novel, biological approach to dentine restoration that stimulates the natural formation of reparative dentine via the mobilisation of resident stem cells in the tooth pulp. Biodegradable, clinically-approved collagen sponges are used to deliver low doses of small molecule glycogen synthase kinase (GSK-3) antagonists that promote the natural processes of reparative dentine formation to completely restore dentine. Since the carrier sponge is degraded over time, dentine replaces the degraded sponge leading to a complete, effective natural repair. This simple, rapid natural tooth repair process could thus potentially provide a new approach to clinical tooth restoration.